A Randomized Trial of Brief Online Interventions to Facilitate Treatment Seeking for Social Anxiety. Issue 5 (September 2022) - Tobias, Margaret R.; Landy, Lauren N.; Levin, Michael E.; Arch, Joanna J.
This study developed and evaluated a brief, single-session online intervention designed to facilitate treatment seeking among adults with clinically significant social anxiety (SA) symptoms, who generally seek treatment at exceptionally low rates. Adults ( N = 267) reporting significant SA symptoms were recruited online and randomized to a brief, single-session online intervention: Education consisted of brief psychoeducation and treatment resources, or Education+Motivation which added treatment seeking-focused motivational content adapted from Motivational Interviewing and Acceptance and Commitment Therapy. Attitudes, intentions, perceived control, and treatment seeking were assessed at Pre, Post, and 1-month follow-up (FU). Both interventions were feasible (90% completion) and improved all outcomes. At FU, 70% reported engaging in one or more SA treatment-seeking behaviors. Education+Motivation was more effective than Education at improving treatment-seeking attitudes and behaviors. A brief online intervention with educational and motivational content is a promising direction for promoting treatment seeking for adults with SA symptoms.